Clinical Characteristics of Adult Uncorrected Secundum Atrial Septal Defect, A Pilot Study - Lucia Krisdinarti; Anggoro Budi Hartopo; Dyah Wulan Anggrahini; Ahmad Hamim Sadewa; Abdus Samik Wahab; Budi Yuli Setianto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2016)
ABSTRACTAtrial septal defect (ASD) is the most frequent congenital heart disease in adulthood. Pulmonary hypertension (PH) complicating ASD compels patients seeking medical assistance because of its disabling symptom. Most adult ASD develop PH which render significant morbidity and mortality. The aim of the study is to characterize the clinical profiles of adult patients with ASD. The study design was cross sectional. The subjects were enrolled consecutively from outpatient clinics and inpatient wards. The demography, medical and imaging data were collected and recorded in case report form. Descriptive statistics was applied to characterize the subjects. Seventy-six subjects were enrolled. The majority were women (77.6 %) in the productive and child-bearing ages (63.2%). The most common symptoms were dyspneu on effort, fatigue, and palpitation. Most subjects had functional capacity of WHO class functional II (70.2 %). The mean oxygen saturation was 96.4 %. Based on the echocardiography examination, 77.6% of subjects had suffered from PH. The mean longest diameter of defects were 2.7 cm. The direction of blood flow was mostly left to right (77.6 %). Left and right ventricle function were within normal limit. Right heart catheterization showed mean left atrial pressure 11.5 mmHg, which confirmed the precapillary or arterial PH. Mean pulmonary artery pressure was 42.0 mmHg. The pulmonary artery resistance index mostly less than 4 Wood Unit/ m2 (63.7 %), indicating the feasibility to close the defect. Whereas 24.6 % of subjects were contraindicated for closing. Pulmonary artery hypertension (PAH) was diagnosed in 77.6 % subjects, meanwhile 13.2 % had borderline PAH. In conclusion, most adult ASD patients had developed PAH, mostly young women in productive ages, mainly visited hospital due to symptom of PH, the direction of flow predominantly left to right side and mostly had reduced functional capacity.